(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
Career maturity is a crucial aspect of vocational education, especially for vocational high school (SMK) students who are in the transition phase from school to work. Various studies show that many SMK students still have low levels of career maturity, characterised by unclear career planning, limited career exploration, and difficulties in career decision-making. This condition emphasises the importance of career guidance services in schools. This study aims to analyse the role of career guidance services in improving the career maturity of SMK students. The method used is a literature study with a qualitative approach to national and international scientific articles published in the last ten years. Data were collected through the Google Scholar, ERIC, Scopus, and Garuda databases, then analysed using content analysis techniques. The results of the study show that career guidance services contribute positively to improving the career maturity of vocational high school students, particularly in the aspects of career planning, career exploration, decision making, affective readiness, and career adaptation skills. These findings also reveal that the effectiveness of career guidance services is greatly influenced by the quality of implementation, suitability to the characteristics of vocational education, and policy and school environment support